The Enigma of Lymphocyte Apoptosis in the Response to Influenza Virus Infection - Norbert J. Roberts (Viruses, 2023)
In the pathogenesis of influenza virus infection, lymphocyte apoptosis as a part of the infection and/or the immune response to the virus can be somewhat puzzling. The percentage of human T lymphocytes within the peripheral blood mononuclear cell population that becomes apoptotic greatly exceeds the percentage that are infected after exposure to the virus, consistent with substantial apoptosis of bystander T lymphocytes. Studies reveal an important role of viral neuraminidase expression by co-cultured monocyte/macrophages in induction of apoptosis, including that of uninfected bystander lymphocytes. Despite these observations, it is a reasonable perspective to recognize that the development of lymphocyte apoptosis during the response to infection does not preclude a successful immune response and recovery of the infected host in the great majority of cases. Further investigation is clearly warranted to understand its role in the pathogenesis of influenza virus infection for human subjects.